Foliar Absorption of Nitrogen and Phosphorus by Cashew - Mini Abraham (Department of Agronomy, College of Horticulture, 1994)
An investigation was undertaken at the College of Horticulture, Kerala Agricultural University, Vellanikkara during 1993-'94 to study the foliar absorption of nitrogen and phosphorus by cashew. The main objectives of the study were to develop a method to study the foilar absorption of 14c-urea and 32p and to identify the factors affecting foliar absorption of nitrogen and phosphorus by cashew. It was also aimed to compare the root absorption with foliar absorption and to study the leaf anatomy of cashew in relation to foliar absorption. The experiment was done using three month old cashew seedlings and six year old cashew trees (var.Anakkayam-l). The salient findings are abstracted below.